PENDAMPINGAN BRANDING PACKAGING DAN DIGITAL MARKETING PADA KERUPUK ATOM KHAS DESA PENGUDANG - Muhammad Mu’azamsyah; Yuritanto Yuritanto; Agustinus Sihombing; Herman Herman; Eko Murti Saputra; Muhammad Adi Wijaya; Eka Fitria Ningsih; Erwin Pebriansyah; Nadya Reza Puspita; Ramdhani Puspita (Bajang Institute, 2023)
KUBE Jaya Abadi atom cracker was established in 2016. The processed food produced by kube is atom cracker which is made from puput fish as the main ingredient. There are problems faced by KUBE Jaya Abadi, among others, first, KUBE Jaya Abadi has difficulty ordering packaging because the packaging is ordered in the Malang area so it requires a large cost. Second, KUBE Jaya Abadi has a small market scope and does not have social media to develop in marketing its products. By seeing the high potential possessed by this kube, group 3 KKN-P2EM STIE PEMBANGUNAN TANJUNGPINANG 2022 created a program that focuses on atom cracker processing, namely branding packaging which aims to further increase sales and marketing of processed products from KUBE and make it easy to order packaging. and also assisting these atom cracker KUBE in utilizing social media to be used as promotional and marketing media.